Kebijakan Regulatif Pemerintah Provinsi Riau terhadap Badan Usaha Milik Desa Tahun 2020-2022 - Adlin, Adlin; Yusri, Ali; Muchtar, Erman; Azwar, Wazni; Yealta, Den (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The intervention of the Riau provincial government through various policies needs to be carried out to develop village-owned enterprises (BUMDes). One form of intervention that has been carried out is formulating a regulatory policy regarding the provision of special financial assistance for the development of BUMDEs, which will be described in this article. The Riau provincial government has made changes to regulatory policies related to the use of Special Financial Assistance (BKK) funds which can be used to develop business units and village-owned businesses. In this case, the Riau provincial government prohibits using BKK funds to establish business units that do not drive the community's economy, banking business units such as savings and loans and financing. The theory used as a reference is the opinion of (Haeder & Yackee), (Goo & Heo) and Saravade et al. Data were collected through interviews and documents and then analyzed qualitatively. This study concludes that regulatory policies have caused changes in the types of BUMDes business units developing in Riau province in 2020-2022.